PENGARUH BAHAN TAMBAHAN TEXAPON TERHADAP KUAT TEKAN BETON RINGAN - Nurjanah (Universitas Islam Balitar Blitar, 2019)
Development in the field of construction is very rapid, including in the construction of housing, hospital offices and so on. Concrete as a building material has long been used and widely applied by the community because it has advantages - advantages over other structural materials which have good strength, fire resistance, resistance to weather changes, and are relatively easy in construction. This research was conducted to determine the effect of substitution with Texafone additives on concrete compressive strength. The method used in this study is to make lightweight concrete substitute for texafon additives by 0%, 10% and 30% of the weight of lightweight Concrete sand which has been cured during 7 days later it was tested to get the compressive strength of lightweight concrete. The results showed the value of 0% substitution strength at 7 days is 6.2 Mpa, while an additional 10% is 5.21 Mpa and an additional 30% is 4.51 Mpa.